The role of alien fish (the centrarchid Micropterus salmoides) in lake food webs highlighted by stable isotope analysis. (10th May 2018) - Costantini, Maria Letizia; Carlino, Pasquale; Calizza, Edoardo; Careddu, Giulio; Cicala, Davide; Sporta Caputi, Simona; Fiorentino, Federico; Rossi, Loreto
Abstract: Non‐native freshwater fish species can have adverse ecological impacts on native populations. However, the mechanisms determining the success or otherwise of their invasion and their role in invaded communities remain largely unknown. This is particularly true for the Mediterranean region, where endemic species characterised by restricted natural ranges may be at high risk of extinction. The largemouth bass ( Micropterus salmoides ) is native to North America but is invasive in the Italian Peninsula. The aim of this study was to explore the trophic position of M. salmoides, its diet and niche overlap with native fish species in the littoral areas of a Mediterranean lake. Our study was supported by analysis of stable C and N isotopes in the tissues of fish and their potential food sources, twenty years after the introduction of the largemouth bass to Lake Bracciano (Italy). Samples were collected in locations varying in terms of physical structure and resource availability at lower trophic levels in the food web, which was greater in the southern (hereafter: South) than in the northern (hereafter: North) area of the lake. These differences made it possible to explore the mechanisms linking environmental conditions and the role of alien predators in the invaded food web. The abundance of M. salmoides was higher, and the diversity of native fish species was lower, in North than South. In North, M. salmoides had a piscivorous diet and occupied a higher trophic position in the food web than in South, where invertebrates constituted an important part of its diet. As a consequence, trophic niche interference with other fish species at intermediate trophic levels was higher in South. In contrast, in North, M. salmoides showed stronger trophic interference with the percid Perca fluviatilis, a native top predator in the food web, but weaker interference with remaining fish species. Our results help to understand the role of alien species in the food webs of Lake Bracciano, which primarily depends on the habitat and the availability of prey across trophic levels. Physical and ecological variations in the habitat were associated with differences in predatory interactions among native and alien fish species. This suggests that a reduction in productivity and biodiversity at lower trophic levels in lake food webs may favour the success of opportunistic invasive fish species, given the ability of the invaders to maintain some of their characteristics silent, and to fully express their genotype under favourable environmental conditions.